2005
DOI: 10.1124/dmd.105.005785
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metabolism of Naphthalene by Human Liver Microsomal Cytochrome P450 Enzymes

Abstract: ABSTRACT:The polycyclic aromatic hydrocarbon naphthalene is an environmental pollutant, a component of jet fuel, and, since 2000, has been reclassified as a potential human carcinogen. Few studies of the in vitro human metabolism of naphthalene are available, and these focus primarily on lung metabolism. The current studies were performed to characterize naphthalene metabolism by human cytochromes P450. Naphthalene metabolites from pooled human liver microsomes (pHLMs) were trans-1,2-dihydro-1,2-naphthalenedio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 29 publications
1
83
0
1
Order By: Relevance
“…CYP isoform screening in this study identified CYP1A2 as the most efficient isoform for producing dihydrodiol and 1-naphthol, and CYP3A4 as the most effective for 2-naphthol production. Whereas further pHLM metabolism of 2-naphthol was found to produce 2,6-and 1,7-dihydroxynaphthalene, dihydrodiol and 1-naphthol were not efficiently metabolized by pHLMs (Cho et al, 2006). CYP1A2 and 2D6*1 were identified as the most active isoforms for producing 1,4-naphthoquinone, and CYP3A4 and CYP2A6 the most active at metabolizing dihydrodiol, though at rates less than those at which 1-naphthol was observed to be metabolized (Cho et al, 2006).…”
Section: Naphthalene Cytotoxicity Requires Metabolic Activation; Unmementioning
confidence: 99%
See 2 more Smart Citations
“…CYP isoform screening in this study identified CYP1A2 as the most efficient isoform for producing dihydrodiol and 1-naphthol, and CYP3A4 as the most effective for 2-naphthol production. Whereas further pHLM metabolism of 2-naphthol was found to produce 2,6-and 1,7-dihydroxynaphthalene, dihydrodiol and 1-naphthol were not efficiently metabolized by pHLMs (Cho et al, 2006). CYP1A2 and 2D6*1 were identified as the most active isoforms for producing 1,4-naphthoquinone, and CYP3A4 and CYP2A6 the most active at metabolizing dihydrodiol, though at rates less than those at which 1-naphthol was observed to be metabolized (Cho et al, 2006).…”
Section: Naphthalene Cytotoxicity Requires Metabolic Activation; Unmementioning
confidence: 99%
“…Whereas further pHLM metabolism of 2-naphthol was found to produce 2,6-and 1,7-dihydroxynaphthalene, dihydrodiol and 1-naphthol were not efficiently metabolized by pHLMs (Cho et al, 2006). CYP1A2 and 2D6*1 were identified as the most active isoforms for producing 1,4-naphthoquinone, and CYP3A4 and CYP2A6 the most active at metabolizing dihydrodiol, though at rates less than those at which 1-naphthol was observed to be metabolized (Cho et al, 2006). Necrosis of bronchial epithelial (Clara) cells in mice (O'Brien et al, 1985(O'Brien et al, , 1989Tong et al, 1981) and necrosis of olfactory epithelial cells in mice, rats and hamsters following intraperitoneal injection of naphthalene strongly indicate that metabolic activation in target tissues plays a dominant, and possibly exclusive, role in site-specific naphthalene cytotoxicity.…”
Section: Naphthalene Cytotoxicity Requires Metabolic Activation; Unmementioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type mice treated (IP injection) with naphthalene and a CYP2F inhibitor (5-PIP) showed no signs of lung or olfactory toxicity, as compared to the mice treated with naphthalene and no inhibitor where toxicity was observed in lung (hemorrhagic lungs) and olfactory tissue (100% sloughing of olfactory mucosa) (Genter et al�, 2006)� This study has been frequently cited in the literature as support that CYP2F is the CYP involved in metabolic activation of naphthalene to its toxic metabolites in mouse lung� Although these studies are supportive, especially in combination with the immunolocalization studies correlating CYP2F with the naphthalene epoxide at the site of injury in mouse lung, it is important to consider that the CYP2F inhibitor (5-PIP) also inhibits CYP2E1, which is also present in mouse lung and rat nose� Therefore, one needs to consider the possibility that CYP2E1 could be involved in naphthalene metabolism� However, the relative activities of these enzymes toward naphthalene needs consideration� Recombinant CYP2F from mice and rats efficiently generates the naphthalene oxide: CYP2F4 from rats (K M = 3 µM, V max = 107 min −1 ) (Baldwin et al�, 2005); and CYP2F2 from mice (K M = 3 µM, V max = 104 min −1 ) (Shultz et al�, 1999)� We did not find any studies that evaluated the activity of rodent CYP2E1 toward naphthalene� However, recombinant CYP2E1 from humans metabolized naphthalene to its 1-naphthol metabolite at a much lower efficiency (K M = 10�1 µM, V max = 8�4 min −1 ) (Cho et al�, 2006)� These data suggest that CYP2F metabolizes naphthalene more efficiently than CYP2E1, but studies comparing both CYPs in humans and rodents would provide stronger evidence as to the relevance of these two CYPs in various species� Studies in CYP2E1 and CYP2F knockout mice, or with inhibitors specific to CYP2E1, would provide useful information in this regard� Accordingly, as shown in Table 3, the mouse lung data provide "some evidence" that CYP2F is the primary CYP involved in metabolism of naphthalene to the epoxide, but more studies are necessary before we can rule out the involvement of CYP2E1 in metabolic activation of naphthalene to its toxic metabolites in mouse lung� CYP2E1 is present in mouse nasal and lung tissues (Simmonds et al�, 2004;Green et al�, 2001)� One possibility might be that CYP2E1 and CY2F2 are both involved in metabolic activation of naphthalene and cytotoxicity� There is some precedent for considering this possibility; a recent study of 1,1-DCE bioactivation and cytotoxicity in murine Clara cells (Simmonds et al�, 2004) suggested that both CYP2F2 and CYP2E1 are involved in 1,1-dichloroethylene (1,1-DCE) bioactivation and lung toxicity� Immunolocalization studies indicated that the rat nasal mucosa (primarily the olfactory epithelium) contains high levels of CYP2F4 (Baldwin et al�, 2004)� In addition, a recent study by Morris and Buckpitt (2009) found that naphthalene metabolism in the rat nose was inhibited after pretreatment with 5-PIP, suggesting that CYP2F is likely responsible, at least in part, for naphthalene metabolism in the rat nose� Therefore, as shown in Table 3, the rat nasal data provide "some evidence" that CYP2F4 is responsible for naphthalene metabo...…”
Section: Since the Cyp2f Inhibitor (5-pip) Also Inhibits Cyp2e1 Coulmentioning
confidence: 89%
“…can metabolize naphthalene to trans-1,2-dihydro-1,2-naphthalenediol (dihydrodiol), 1-naphthol and 2-naphthol; further pHLM metabolism of 2-naphthol produces 2,6-and 1,7-dihydroxynaphthalene, whereas dihydrodiol and 1-naphthol are not efficiently metabolized by pHLMs (Cho et al, 2006).…”
Section: Naphthalene Metabolite Cytotoxicitymentioning
confidence: 99%